Pendekatan Sistem Dalam Kepemimpinan Kepala Madrasah di (MIS) Al-Hikmah Kecamatan Namorambe Kab Deliserdang - Makmur Syukri; Facruddin Facruddin; Mhd Alfi Syahrin; Rina Hidayah Tambusai; Farihin Abdillah Fattah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This is research of discusses the efforts to increase the competence of teachers through a system of principal leadership. Leadership is an attempt to influence others to do the activity in order to achieve a common goal. Leadership has a strategic role in determining whether or not an organization forward. As supreme leader, the principal has a duty and a vital role in improving the quality of human resources in it. In order to realize the quality of human resources professionals, principals must have the appropriate strategy; educational supervision, education and training, provision of motivation continue, changes in work culture, so that teacher competence as a basic element of education can be realized. The competencies include; pedagogical competence, personal competence, social competence and professional competence.